Answer:
Step-by-step explanation:
If an exponential function is in the form of y = a(b)ˣ,
a = Initial quantity
b = Growth factor
x = Duration
Condition for exponential growth → b > 1
Condition for exponential decay → 0 < b < 1
Now we ca apply this condition in the given functions,
1). ![y=3.2(1+0.45)^{2x}](https://tex.z-dn.net/?f=y%3D3.2%281%2B0.45%29%5E%7B2x%7D)
Here, (1 + 0.45) = 1.45 > 1
Therefore, It's an exponential growth.
2). ![y=(0.85)^{3x}](https://tex.z-dn.net/?f=y%3D%280.85%29%5E%7B3x%7D)
Here, (0.85) is between 0 and 1,
Therefore, it's an exponential decay.
3). y = (1 - 0.03)ˣ + 4
Here, (1 - 0.03) = 0.97
And 0 < 0.97 < 1
Therefore, It's an exponential decay.
4). y = 0.5(1.2)ˣ + 2
Here, 1.2 > 1
Therefore, it's an exponential growth.